IPTEKS PENGENDALIAN INTERN ASET TETAP FISKAL PADA PT. PLN (PERSERO) UNIT INDUK WILAYAH SULUTTENGGO - Sinjal, Jordy; Runtu, Treesje (Jurnal Ipteks Akuntansi Bagi Masyarakat, 2018)
PT. PLN (Persero) is stated-owned enterprises of Indonesia that engaged in electricity aspect. PT. PLN (Persero) is demanded by the government to increase social mission and seek profits. The main objective of PT. PLN (Persero) is to distribute electricity to the Indonesian society equally. many buildings, machinery, property and administrative equipment owned by PT. PLN (Persero) must be managed appropriately. Therefore, it takes internal control of fixed assets well to improve employee performance and productivity. A well internal control is needed to keep the fixed assets of a company or entity maintaining the useful life of fixed assets to ease the company operations. Based on the observations of PT. PLN (Persero), internal control of fixed assets already effective and efficient, but there are few things that needs to be concerned such as the completeness of documents and archiving. Archiving is really important for a company because archive is a copy of document made and accepted as a requirement to be fulfilled for administration material, or for material copies or material experience if there is a loss of the original archive.Keywords: Fixed Assets, Internal Control, Completeness of Documents, and Archiving